The application of coastal management and Geographical Information System (GIS) initiatives in Selangor from government agencies perspectives - Paiman, Tuminah; Asmawi, M. Zainora; Mohamed, Mohd Zin (2016)
It is well recognised that coastlines are undergoing rapid development and firm management policies have to be made. Nevertheless, for any shore management to be efficacious, the policies need to be founded on informed decision-making. Geographical Information System (GIS) encourages the development and use of standards for coastal data definition, collection and storage, which promotes compatibility of data and processing techniques between projects and departments, as well as ensuring consistency of coastal management approach. Purpose of this research to find a perception from government agencies that has used GIS in managing coastal area in Selangor. Two main divisions of coastal change analysis may be recognized: monitoring and simulation modelling. GIS modelling and simulation of coastal phenomena are extremely valuable techniques for assessing the effectiveness and likely impacts of such intervention. Thus, a well-designed coastal area information system could be a significant decision support tool to aid the development of integrated and sustainable coastal resource management strategies.